White Scholars/African American Texts - Long, Lisa (Book collections on Project MUSE., 2005)
The essays in this collection explore the many difficulties created by the fact that white scholars greatly outnumber black scholars in the study and teaching of African American literature. Contributors, including some of the most prominent theorists in the field as well as younger scholars, examine who is speaking, what is being spoken and what is not, and why framing African American literature in terms of an exclusive black/white racial divide is problematic and limiting. In highlighting the ""whiteness"" of some African Americanists, the collection does not imply that the teac.